Case Report: J-Shaped External Fixator for Treatment of Mayo Type II Olecranon Fractures – A Novel Surgical Technique and Report of Clinical Applications - Tian, Yue; Ge, Xin; Zou, Jiyang; Song, Fenglei; Cheong, John Chun tien chui wan; Ge, Changqing; Zhang, Weiguo; Li, Jie; Tian, Kang (Frontiers in Surgery, 2022)
Purpose We designed a J-shaped external fixator (J-EF) to provide a minimally invasive, one-step surgical method for olecranon fractures. The aim of this study is to retrospectively review the method and the outcomes in 14 patients treated with J-EF fixation. Methods Biomechanical comparative study was performed to test the tensile properties of the J-EF using a universal testing machine. Between January 2002 and December 2005, 14 patients (age range: 25–67 years) with Mayo type II olecranon fractures were treated using the external fixation technique. Follow-up was done by standard measures (radiography, range of motion, and complications monitoring) and patient-reported outcomes (Mayo Elbow Performance Score [MEPS] and Disabilities of the Arm, Shoulder, and Hand [DASH] scores) 6 months after surgery. Eight of the patients were reviewed 15 years after the surgery. Results Results from biomechanical studies indicate the non-inferiority of J-EF to tension-band wiring (TBW) in tensile properties. At the time of release, the mean elbow flexion arc was 132.5° and the mean forearm rotation arc was 173.6°. The mean DASH score was 14.1 points, and the mean MEPS was 93.9 points. Operative time and intraoperative blood loss were decreased by 41.3% and 64.6%, respectively, in J-EF patients than those in a comparable group treated by TBW. All eight patients are still alive after the surgery and maintaining the original outcome. Conclusions External fixation using the J-EF could be considered as an alternative treatment for Mayo type II olecranon fractures as it appears to be a reliable, minimally invasive, and time-saving. Level of Evidence Therapeutic Level IV.